Oral peptide delivery: challenges and the way ahead. Issue 4 (April 2021) - Dubey, Sunil Kumar; Parab, Shraddha; Dabholkar, Neha; Agrawal, Mukta; Singhvi, Gautam; Alexander, Amit; Bapat, Ranjeet Ajit; Kesharwani, Prashant
Highlights: Oral route of administration is the preferred route for drug delivery. Dosage form designing plays an essential role in oral peptide delivery. Preclinical and clinical aspects of oral peptide delivery have been reviewed. It will help to understand & invent novel approaches for oral peptide delivery. Abstract : Peptides and proteins have emerged as potential therapeutic agents and, in the search for the best treatment regimen, the oral route has been extensively evaluated because of its non-invasive and safe nature. The physicochemical properties of peptides and proteins along with the hurdles in the gastrointestinal tract (GIT), such as degrading enzymes and permeation barriers, are challenges to their delivery. To address these challenges, several conventional and novel approaches, such as nanocarriers, site-specific and stimuli specific delivery, are being used. In this review, we discuss the challenges to the oral delivery of peptides and the approaches used to tackle these challenges. Teaser: This review discusses the challenges in oral delivery of peptides and novel approaches used to tackle them.